The Effect of Transparency, Performance Evaluation, and Financial Reporting on Achieving Budget Targets - RA, Suhaimi (International Journal of Advanced Multidisciplinary, 2023)
The Effect of Transparency, Performance Evaluation and Financial Reporting on Budget Target Achievement is a scientific article of literature study in the scope of financial management. The purpose of this article is to build a hypothesis of influence between variables that will be used in further research. The object of research on online libraries, Google Scholar, Mendeley and other academic online media. Research methods with library research sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Transparency affects Budget Target Achievement; 2) Performance Evaluation affects the Achievement of Budget Targets; and 3) Financial Reporting affects Budget Target Achievement.